New Approaches to Inequality Research with Youth: Theorizing Race Beyond the Traditions of Our Disciplines - Tuck, Eve (Taylor & Francis Group, 2024)
This edited volume shares contributors' first-person narrations of some of the hard-fought learnings and challenges of breaking from the traditions of their disciplinary fields and finding new and reclaimed ways to think about race.